식품 제조를 위한 식품 3D 프린터 기술 리뷰 - 변지현(Jihyun Byun); 김상오(Sang-oh Kim) (한국식품과학회지, 2024)
이 리뷰에서는 4차 산업혁명(Fourth Industrial Revolution; FIR) 에서 3D 프린터가 식품 제조 기술에 활용되는 방안에 대해서 고찰해 보았다. FIR은 디지털 기술, 자동화, 인공 지능과 같은 혁신을 통해 산업 전반에 걸쳐 중요한 변화를 가져왔다. 식품 제조를 위한 공정도 이러한 변화의 흐름을 잇기 위해 많은 시도를 하고 있다. 특히, 다축 모터 제어를 이용한 3D 프린터의 등장은 식품 산업을 비롯한 다양한 산업 분야에서 활용도가 확대됐다. 제조 공정 내 특정 작업을 처리하기 위해 식품 생산에 3D 프린터를 활용하는 데 대한 관심이 높아지고 있다. 이 리뷰에서는 식품산업의 혁신적인 기술을 간략하게 설명하고 다양한 유형의 3D 프린터와 인쇄 방법을 요약하고 식품을 생산하기 위한 활용도에대해 논의했다. 또한, 식품 3D 프린터에 적합한 소재를 탐색하였고 향후 연구 방향에 대해 제시하였다. This review describes how 3D printers can be used in food manufacturing technology in the Fourth Industrial Revolution, which involved adopting innovations such as digital technology, automation, and artificial intelligence. Technological trends are currently being implemented in food manufacturing processes. Notably, the advent of 3D printers with multi-axis motor control has expanded their utility across various industries, including the food industry. There is growing interest in utilizing 3D printers in food production to perform specific tasks within the manufacturing process. The review outlines the revolutionary technologies in the food industry, highlights different types of 3D printers and their printing methods, and discusses their current utilization in food production. Furthermore, suitable materials for food 3D printers and future research directions are explored. KCI Citation Count: 2